Barriers to the implementation of advanced clinical pharmacy services at Portuguese hospitals - Brazinha, Isabel (2015)
Background In some countries, such as Portugal, clinical pharmacy services in the hospital setting may be implemented to a lower extent than desirable. Several studies have analysed the perceived barriers to pharmacy service implementation in community pharmacy. Objective To identify the barriers towards the implementation of advanced clinical pharmacy services at a hospital level in Portugal, using medication follow-up as an example. Setting Hospital pharmacies in Portugal. Methods A qualitative study based on 20 face-to-face semi-structured interviews of strategists and hospital pharmacists. The interview guide was based on two theoretical frameworks, the Borum’s theory of organisational change and the Social Network Theory, and then adapted for the Portuguese reality and hospital environments. A constant comparison process with previously analysed interviews, using an inductive approach, was carried out to allow themes to emerge. Themes were organised following the Leavitt’s Organizational Model: functions and objectives; hospital pharmacist; structure of pharmacy services; environment; technology; and medication follow-up based on the study topic. Main outcome measure Barriers towards practice change. Results Medication follow-up appeared not to be a well-known service in Portuguese hospital pharmacies. The major barriers at the pharmacist level were their mind-set, resistance to change, and lack of readiness. Lack of time, excessive bureaucratic and administrative workload, reduced workforce, and lack of support from the head of the service and other colleagues were identified as structural barriers. Lack of access to patients’ clinical records and cumbersome procedures to implement medication follow-up were recognised as technological barriers. Poor communication with other healthcare professionals, and lack of support from professional associations were the major environmental barriers. Conclusion Few of the barriers identified by Portuguese hospital pharmacists were consistent with previous reports from community pharmacy. The mind-set of pharmacists and predetermined attitudes are recognised as barriers that can give rise to new perceived barriers.